Effect of Strategic Leadership on Competitive Advantage of Animal Feeds Manufacturing Firms in Upper Eastern and Central Kenya - Kairira, Peter Mwika; Obuba, Robert (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: Over time, enhancing a company's performance had mainly involved securing a competitive position compared to industry peers. A competitive advantage results in improved performance by cultivating greater customer loyalty, heightened satisfaction, improved financial outcomes, and a larger market share. As a result, organizations were increasingly working to strategically position themselves within their industries to surpass competitors. Despite implementing various strategic changes to maintain a competitive edge, companies in the animal feed manufacturing sector, including those in the central and upper east regions of Kenya, confront intense competition from both established and new players. This study aimed to evaluate the impact of strategic leadership on the competitive advantage of animal feed manufacturing firms in Upper Eastern and Central Kenya. Design/methodology/approach: The competitive advantage theory will provide insights into the research. Employing an explanatory research design, the study focused on 96 animal feed manufacturing firms in Central and Upper Eastern Kenya. The research adhered to ethical standards and principles, presenting the findings through charts and tables. Charts and tables were utilized to present the findings of the study. Findings: The conclusions drawn from the results suggest that the adoption of strategic leadership exhibits a constructive and considerable influence on competitive advantage within Animal feeds manufacturing firms in Central and Upper Eastern Kenya. The study advises animal feeds manufacturing firms to prioritize bolstering strategic leadership across managerial echelons, from mid-level managers to top executives, to ensure they grasp their responsibilities in fostering and preserving competitive advantage over the long haul. Paper type: Research paper